2016
DOI: 10.4236/ojgas.2016.63012
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Trial on the Efficacy and Safety of a Natural Mineral Water Rich in Hydrogen Carbonate on Functional Dyspepsia and Heartburn

Abstract: Background: Dyspepsia and heartburn are among the most frequent complaints of the upper gastrointestinal tract impacting quality of life. The present study aimed to investigate the impact of drinking a natural mineral water (medicinal product category "Heilwasser" in Germany) high in hydrogen carbonate (Staatl. Fachingen STILL) on functional dyspeptic complaints and heartburn. Methods: 56 men and women with self-reported heartburn were enrolled to this one-arm pilot study. They had to drink 1.5 L of a hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The two studies with good methodological quality ratings (for pre-post experiments) were funded by producers of mineral waters. Using hydrogen carbonate-rich mineral waters, both studies showed considerable reductions in the frequency and duration of heartburn episodes after 6 weeks [ 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The two studies with good methodological quality ratings (for pre-post experiments) were funded by producers of mineral waters. Using hydrogen carbonate-rich mineral waters, both studies showed considerable reductions in the frequency and duration of heartburn episodes after 6 weeks [ 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of the six single arm intervention studies, only two were rated as having good quality, for studies with pre-post comparisons [ 45 , 47 ]. Both studies examined 1.5 L (per day) of hydrogen carbonate-rich mineral water for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, mineral water with various electrolyte compositions has been utilized in the treatment of functional gastrointestinal diseases; mineral water supplements have been reported to improve functional dyspepsia associated with IBS by controlling gastric acid output and intestinal transit time [ 17 ]. In addition, carbonated water not only attenuates the hunger but also improves dyspeptic symptoms and heartburn [ 18 , 19 ]. Drinking sulfur-rich mineral water for more than three weeks was found to be effective in treating constipation by increasing frequency of bowel movements [ 20 ].…”
Section: Introductionmentioning
confidence: 99%